MitigatePlus: Low-Emission Food Systems - Verchot, Louis V.; Zhang, Wei (International Food Policy Research Institute, 2022)
The Mitigate+: Low-Emission Food Systems Initiative focuses on reducing GHGE from food systems in target countries by 1.1 gigatons per year (6.5 percent) by 2030, thus mitigating the predicted impact of climate change on sustainable development and social equity. The approach is consistent with the Paris Agreement, which aims to foster low-emission development without negatively impacting food production. An estimated 8 million people will benefit from these reduced emissions and associated benefits over the Initiative’s 10-year lifespan.